Engineering characteristics of the compressed-stabilized earth brick - Agus Setyo Muntohar (ELSEVIER, 2011)
Utilization of lime and rice husk ash for soil stabilization produced considerable strength gain and other geotechnical properties of the stabilized soils. Its application could be also superior for construction materials as compressed-stabilized earth (CSE) or unfired-brick. This paper presents the investigation result of the application of lime and rice husk for unfired brick or compressed stabilized earth. The compressive and three-point flexural strength tests including compressive strength after water submersion were carried out in this present study. The investigation results show that compressive and flexural strength of clay brick are improved by adding of lime and RHA. The best quantity of lime and RHA in this study, is obtained by ratio 1:1 of lime and RHA. The addition of sand in stabilized clay resulted in more improvement in the water retention ability.